Effects of sodium‐glucose cotransporter 2 inhibitors on risk of venous thromboembolism in patients with type 2 diabetes: A systematic review and meta‐analysis. Issue 1 (27th May 2019) - Wang, Aihua; Yang, Keming; Wang, Tiansheng; Zhang, Ning; Tang, Huilin; Feng, Xin
Summary: It has been reported that sodium‐glucose cotransporter 2 (SGLT2) inhibitors could increase blood viscosity, which may further increase risk of venous thromboembolism (VTE). Therefore, we conducted this meta‐analysis to evaluate the association between SGLT2 inhibitors and risk of VTE in patients with type 2 diabetes. We systematically searched electronic databases up to April 2019 to identify randomized trials that reported the events of VTE in SGLT2 inhibitors group and control group (placebo or other active antidiabetic drugs). The primary outcome was VTE, and secondary outcomes included deep venous thrombosis (DVT) and pulmonary embolism (PE). A fixed‐effects meta‐analysis was performed to calculate the risk ratio (RR) with 95% CI. In total, 29 randomized trials involving 56 035 patients with type 2 diabetes were included. Incidence of VTE was not significantly different between SGLT2 inhibitors group and control group (128/32 038 vs 92/23 997), yielding an RR of 0.98 (95% CI, 0.75‐1.28). Similarly, null associations were observed in the subgroup analyses. Our cumulative meta‐analysis demonstrated the stability of our overall result over time. There was no significant association between SGLT2 inhibitors and risk of both DVT (17 trials; 31/17 442 vs 15/10 930; RR, 1.06; 95% CI, 0.60‐1.89) and PE (19 trials; 56/26 118 vs 41/19 517; RR, 0.99; 95% CI, 0.67‐1.46). Low statistical heterogeneity and no evidence of publication bias were observed. Current evidence from randomized trials found no association between SGLT2 inhibitors and risk of VTE among patients with type 2 diabetes.